The Influence of Financial Literacy and Lifestyle on Financial Management Behavior in College Students - Fadila Sardita; Friyatmi Friyatmi (Journal of Innovative and Creativity, 2026)
Financial literacy and lifestyle are important factors in shaping students' financial management behavior. However, studies examining the influence of these two variables simultaneously and the gap between financial management knowledge and practice are still limited. This study aims to analyze the influence of financial literacy and lifestyle on the financial management behavior of undergraduate students in the Faculty of Economics and Business, Padang State University. This study used a quantitative approach with an associative survey design. The population in this study were undergraduate students of the Faculty of Economics and Business, Padang State University, with a sample of 97 respondents selected using proportional random sampling technique. Data were collected through a closed-ended Likert-scale questionnaire to measure lifestyle and financial management behavior, and an objective multiple-choice test to measure financial literacy. The obtained data were analyzed using multiple linear regression analysis techniques. The results showed that partially financial literacy did not significantly influence students' financial management behavior. Conversely, lifestyle had a positive and significant effect on financial management behavior. Simultaneously, financial literacy and lifestyle significantly influenced students' financial management behavior with a contribution of 24.8%. The conclusion of this study indicates a knowledge-action gap among students, namely a condition where the level of financial knowledge is not fully reflected in financial management behavior. Furthermore, lifestyle is a more dominant factor influencing students' financial decisions. This research provides theoretical and practical implications for the development of financial education that focuses not only on increasing knowledge but also on developing a controlled and financially responsible lifestyle.